2022
DOI: 10.1155/2022/1389137
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Vaccination against Respiratory Tract Diseases, Including Pneumonia, Influenza, and COVID-19 in Patients with Diabetes Mellitus

Abstract: Patients with diabetes have an increased risk of severe acute respiratory infections, and vaccination is their life-saving option. This study aimed to investigate the interest and knowledge of patients about influenza, pneumonia, and COVID-19(coronavirus disease 2019) vaccines. Materials. We handed out a questionnaire to patients with diabetes who were admitted to the endocrinology clinic between April and August 2021. The questionnaire collected information on demographic data, knowledge about respiratory tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
1
2
Order By: Relevance
“…In contrast, other studies reported lower vaccination rates (4.8%) [31]. Overall, the rate in our study was unsatisfactory compared to studies from Saudi Arabia (84.8 %) [11], Turkey (73.6%) [32], and Iran (62.7%) [6]. This pointed to the lack of direct evidence that vaccinations benefit patients with diabetes, concerns about the vaccination's composition, and side effects that resulted in resistance to vaccine uptake among DM patients [31].…”
Section: Discussioncontrasting
confidence: 98%
“…In contrast, other studies reported lower vaccination rates (4.8%) [31]. Overall, the rate in our study was unsatisfactory compared to studies from Saudi Arabia (84.8 %) [11], Turkey (73.6%) [32], and Iran (62.7%) [6]. This pointed to the lack of direct evidence that vaccinations benefit patients with diabetes, concerns about the vaccination's composition, and side effects that resulted in resistance to vaccine uptake among DM patients [31].…”
Section: Discussioncontrasting
confidence: 98%
“…We investigated 300 hospitalized COVID-19 patients with a variety of demographic, clinical, and laboratory profiles. In the current study, the vaccination coverage was 9.33%, which was low in comparison to studies from Iran, 14 Turkey, 15 Saudi Arabia, 16 and India. 17 On the contrary, only few studies reported a lower vaccination coverage for e.g.…”
Section: Discussioncontrasting
confidence: 88%
“…On the contrary, multiple previous studies have reported a significant positive correlation between higher educational levels and increased vaccination rates. For instance, a study conducted in Turkey aimed at determining vaccine awareness among patients with DM found a significant positive correlation between influenza vaccine acceptance and education level, suggesting that a higher education level increases the likelihood of accepting the vaccine[ 25 ]. Similarly, a study in Turkey also determined that receiving pneumococcal and influenza vaccinations is associated with higher education levels in patients with DM[ 26 ].…”
Section: Discussionmentioning
confidence: 99%